2021
DOI: 10.3390/cancers13061266
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multimodal Analgesia for Postoperative Pain Management in Head and Neck Cancer Patients

Abstract: Postoperative opioid use has been linked to the subsequent development of opioid dependency. Multimodal analgesia (MMA) can reduce the use of opioids in the postoperative period, but MMA has not been well-studied after major head and neck surgery. Our goal is to explore the association between MMA and postoperative opioid use and pain control in patients undergoing major head and neck surgery. We performed a retrospective study in adult (age 18 years) patients undergoing primary head and neck cancer resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…The benefit of goal-directed fluid therapy may be marginal [37], but adequate pain control is expected to facilitate early mobilization. We have previously shown that the introduction of an opioid-sparing pain management protocol increased the proportion of patients with adequate pain control (pain rating below 4/10) by ~10% in the first 24 h after surgery [38]. Changes in pain management in our study could have contributed to compliance with the pathway recommendation, but it cannot account for the decrease in time to mobilization after the introduction of the new mobilization recommendation in February 2016 (Figure 1).…”
Section: Discussionmentioning
confidence: 65%
“…The benefit of goal-directed fluid therapy may be marginal [37], but adequate pain control is expected to facilitate early mobilization. We have previously shown that the introduction of an opioid-sparing pain management protocol increased the proportion of patients with adequate pain control (pain rating below 4/10) by ~10% in the first 24 h after surgery [38]. Changes in pain management in our study could have contributed to compliance with the pathway recommendation, but it cannot account for the decrease in time to mobilization after the introduction of the new mobilization recommendation in February 2016 (Figure 1).…”
Section: Discussionmentioning
confidence: 65%
“…The findings of Clark, et al [10] support those of Kiong, et al [12] and Jandali, et al [11] in demonstrating lower post-operative peak pain scores (4.6 ± 3.6 vs. 6.5 ± 3.5 (p = 0.004)) and lower morphine milligram equivalents in the ERAS group in comparison to the non-ERAS cohort (6.0 ± 9.8 vs. 10.3 ± 10.8 (p = 0.010)). Hinther, et al [14] compared patients on a multi-modal analgesia (MMA) protocol with those on a 'pre-MMA' pathway. Average daily opioid consumption was lower in the MMA group (29.7 mg vs. 43.3 mg (p = 0.04)) and pain was managed more effectively for the first 6 days postoperatively using an MMA approach.…”
Section: Post-operative Pain Scores and Analgesic Requirementsmentioning
confidence: 99%
“…6. Implement a multimodal approach, including specialist referral: consider referral of patients at high risk of substance abuse [53][54][55][56].…”
Section: Universal Precautions To Limit Non-medical Opioid Usementioning
confidence: 99%